PENDIDIKAN TAUHID MELALUI METODE BERPIKIR RASIONAL-ARGUMENTATIF - Fitriyani Rismawati (Jurnal Pendidikan Agama Islam, 2016)
God sent His servant thinks to find faith, but in reality the majority of muslims with an identity crisis by simply accept the doctrine without thinking process. Felix Siauw as a convert to Islam who believe the thought, share the concept of rational-argumentative thinking to guides Muslims in their faith. This research is axpected to be used to develop a way of thinking Muslims in growing faith. This research is a literature with a philosophical approach that is collected with documentation. The analysis is done by identifying the contents of the book, then analyzed and confirmed by the data, and then draw up a classification so that it can be deduced. The thought process with this method is to find the answer to basic questions and keep asking until you are sure of the existence of God’s existence and consciousness in the worship of God. This method also touches a component in the education of monotheism namely methods, approaches and media.